2010
DOI: 10.1097/md.0b013e3181e9441b
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Nephrotoxicity Caused by Amphotericin B Lipid Complex and Liposomal Amphotericin B

Abstract: Lipid preparations of amphotericin B, commonly used to treat fungal infections, have been demonstrated to have reduced nephrotoxicity compared to conventional amphotericin B. However, to our knowledge, a comprehensive comparison of nephrotoxicity induced by different lipid preparations of amphotericin B has not been performed. We conducted a meta-analysis to evaluate nephrotoxicity associated with amphotericin B lipid complex (ABLC) and liposomal amphotericin B (L-AmB). We searched the PubMed MEDLINE database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 31 publications
2
50
0
12
Order By: Relevance
“…5,15 Sin embargo, esos resultados no son concluyentes. 9,11,[15][16][17] Tres aspectos a tener en cuenta son: la definición de nefrotoxicidad según los diferentes autores; 20 que la creatininemia puede subestimar el filtrado glomerular 25 y que no hay estudios a largo plazo sobre la evolución del compromiso renal.…”
Section: Efectos Adversosunclassified
“…5,15 Sin embargo, esos resultados no son concluyentes. 9,11,[15][16][17] Tres aspectos a tener en cuenta son: la definición de nefrotoxicidad según los diferentes autores; 20 que la creatininemia puede subestimar el filtrado glomerular 25 y que no hay estudios a largo plazo sobre la evolución del compromiso renal.…”
Section: Efectos Adversosunclassified
“…Although the new lipid formulations of AmB have a lower frequency of nephrotoxicity in comparison with AmB-DOC, they all exhibit this adverse effect in a considerable number of patients (10,11,12). AmB most likely produces renal injury by a variety of mechanisms; however, the exact nephrotoxic mechanism remains an open question (2,13).…”
mentioning
confidence: 99%
“…Despite the improved safety features, patients receiving L-AmB may still experience infusion reactions such as fever, chills and rigors and renal toxicity. A recent meta-analysis demonstrated that the probability of experiencing nephrotoxicity during treatment with daily L-AmB (doses 3-10 mg/kg) for invasive fungal infections (IFIs) in patients with hematological malignancies ranged from 2.8 to 32% [9].…”
Section: Introductionmentioning
confidence: 99%